2020
DOI: 10.3390/en13010180
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Enhanced Control of Hybrid Full Bridge–Half Bridge MMCs for HVDC Grid Studies

Abstract: Modular multilevel converters (MMCs) are expected to play an important role in future high voltage direct current (HVDC) grids. Moreover, advanced MMC topologies may include various submodule (SM) types. In this sense, the modeling of MMCs is paramount for HVDC grid studies. Detailed models of MMCs are cumbersome for electromagnetic transient (EMT) programs due to the high number of components and large simulation times. For this reason, simplified models that reduce the computation times while reproducing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…AVM offers almost identical results in all scenarios with a reduced computational burden, but it is infeasible for converter start-up studies. In [111], simplified arm evenin equivalent model for hybrid MMCs has been proposed and validated against DM for steady-state and transient conditions (AC and DC faults). It has been observed that the simplified model of hybrid HBMMC and FBMMC offers accurate and 50 times faster simulation time.…”
Section: Modelling Issues and Challenges Of MMC For Mtdc Gridsmentioning
confidence: 99%
“…AVM offers almost identical results in all scenarios with a reduced computational burden, but it is infeasible for converter start-up studies. In [111], simplified arm evenin equivalent model for hybrid MMCs has been proposed and validated against DM for steady-state and transient conditions (AC and DC faults). It has been observed that the simplified model of hybrid HBMMC and FBMMC offers accurate and 50 times faster simulation time.…”
Section: Modelling Issues and Challenges Of MMC For Mtdc Gridsmentioning
confidence: 99%
“…The HB-SM is the most widely applied topologies of MMC for DC power girds due to the simple structure and low cost. However, MMC rhat is based on HB-SM cannot block the fault currents fed from the AC grid [44], as shown in Figure 10a. Without DC CBs, it can only clear DC fault line by tripping the AC circuit breakers [45].…”
Section: Topologies With DC Fault Ride Through Capabilitymentioning
confidence: 99%
“…Modular multi-level converter (MMC) has emerged as the preferred choice for voltage source converter (VSC)-based HVDC systems mainly due to low losses, low harmonic distortion, scalability, and redundancy [1,2]. However, the control design for an MMC is more challenging as compared to a conventional two-level VSC, which is due to the extra control actions required for the regulation of the internal energy balances.…”
Section: Introductionmentioning
confidence: 99%
“…Once the two linear models are derived, the system stability is studied and the critical modes are identified through The average-value model of the MMC structure connected to an AC network is presented in Figure 2. Compared to the detailed model, the IGBTs of submodules are not explicitly modeled and the MMC dynamics are represented by controlled voltage and current sources [2,28,29]. In [30], it has been shown that the average-value model accurately replicates the dynamic performance of the detailed model, and it is significantly more efficient for simulation time steps.…”
mentioning
confidence: 99%